Efektivitas Penggunaan Kahoot untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Dasar-Dasar Teknik Ketenagalistrikan - Vina Athiyah Rahmasari; Usmeldi Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research aims to determine the effectiveness of using Kahoot to improve the learning outcomes of class X TL students at SMK Negeri 1 West Sumatra. Student learning outcomes are still low which is caused by the media used in learning being less attractive, thus affecting students' activeness in capturing learning material. Therefore, it is necessary to carry out research using Kahoot to see its effectiveness on student learning outcomes. This research uses a type of experimental research which is categorized into a type of quasi-experimental research with a pretest-posttest control group design. The subjects of this research were class X TL students at SMK Negeri 1 West Sumatra in the 2023/2024 academic year, consisting of 30 students. To measure this effectiveness, a pretest was given before using Kahoot in learning. The posttest is given after the learning process of Basics of Electrical Engineering using Kahoot. The posttest results that have been given are then analyzed using a series of tests such as the prerequisite test, N-Gain Score and Effect Size. After the test results were carried out, there was an increase in the scores of students who used Kahoot compared to classes who did not use it. Student learning outcomes after using Kahoot increase. So Kahoot is effective in improving student learning outcomes.